2009
DOI: 10.1590/s0044-59672009000300020
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação dos efeitos da radiação gama nos teores de carotenóides, ácido ascórbico e açúcares do futo buriti do brejo (Mauritia flexuosa L.)

Abstract: RESUMOBuriti do Brejo (Mauritia flexuosa L.) é um típico fruto da Amazônia, Nordeste e Centro-Oeste brasileiro, muito utilizado na culinária para produção de sucos, doces e vinhos. É considerado uma excelente fonte de carotenóides precursores da vitamina A, apresentando maior concentração de β-caroteno. Além dos carotenóides também encontramos ácido ascórbico e açúcares. O ácido ascórbico administrado em quantidades suficientes pode prevenir os sinais clínicos de deficiência conhecida como escorbuto. O emprego… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 9 publications
(13 reference statements)
1
6
1
3
Order By: Relevance
“…Lima et al (2009) studied Buriti from the state of Goiás and found β carotene values of 31220 μg / 100 g and α carotene values of 5352 μg / 100 g, being both higher than those found in DOI 10.1590/0100-29452017 864 Jaboticabal -SP ANTIOXIDANT ACTIVITY AND PHYSICOCHEMICAL CHARACTERISTICS OF BURITI ... this work. Agostini-Costa et al (2003) studied the influence of freezing and storage on the α and β carotene content in acerola pulp and found that over time, there may be a reduction of up to 63% in β carotene content, and there is no loss of α carotene.…”
Section: Resultsmentioning
confidence: 41%
See 1 more Smart Citation
“…Lima et al (2009) studied Buriti from the state of Goiás and found β carotene values of 31220 μg / 100 g and α carotene values of 5352 μg / 100 g, being both higher than those found in DOI 10.1590/0100-29452017 864 Jaboticabal -SP ANTIOXIDANT ACTIVITY AND PHYSICOCHEMICAL CHARACTERISTICS OF BURITI ... this work. Agostini-Costa et al (2003) studied the influence of freezing and storage on the α and β carotene content in acerola pulp and found that over time, there may be a reduction of up to 63% in β carotene content, and there is no loss of α carotene.…”
Section: Resultsmentioning
confidence: 41%
“…Carotenoids, in addition to being natural dyes, have beneficial effects on human health such as provitamin A activity, increased immune response and reduced risk of degenerative diseases such as cancer, muscle degeneration, cataracts and cardiovascular diseases. Ascorbic acid, also called vitamin C, is important in the formation of teeth and bones and in the prevention of diseases such as scurvy, influenza and heart diseases (LIMA et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The native buriti pulp from Goiás presented a total carotenoid concentration of 349.93 µg/g, on a wet basis, higher than the values reported by Cândido, Silva and Agostine-Costa (2015) of 311.3 µg/g for fruits from the same region, but lower than those of the fruits from Goiás studied by Lima et al (2009) of 446.0 µg/g. However the results observed for the buriti pulp from Tocantins of 632.20 µg/g were higher than those observed for buriti pulps from Pará (528.6 µg/g) (Cândido et al, 2015), Amazon (513.87 µg/g) (Rosso & Mercadante, 2007) and from the north and northeast of Brazil (142 µg/g) (Barreto et al, 2009).…”
Section: C) Total Carotenoidscontrasting
confidence: 59%
“…Assim, a ação favorável do creme de buriti talvez seja decorrente de uma ação sinérgica entre os diversos compostos presentes no óleo. O que pode justificar o processo de cicatrização apresentado 20 .…”
Section: Discussionunclassified